Hip Arthroscopic Management Can Improve Osteitis Pubis and Bone Marrow Edema in Competitive Soccer Players With Femoroacetabular Impingement. Issue 2 (February 2019) - Saito, Masayoshi; Utsunomiya, Hajime; Hatakeyama, Akihisa; Nakashima, Hirotaka; Nishimura, Haruki; Matsuda, Dean K.; Sakai, Akinori; Uchida, Soshi
Background: There is a dearth of knowledge regarding the correlation between femoroacetabular impingement (FAI) and osteitis pubis (OP) among symptomatic soccer players. Purpose: To elucidate whether arthroscopic FAI correction is effective for young competitive soccer players with FAI combined with OP or perisymphyseal pubic bone marrow edema (BME). Study Design: Case series; Level of evidence, 4. Methods: A total of 577 consecutive patients who underwent arthroscopic FAI correction were retrospectively reviewed with a minimum 2-year follow-up. Competitive soccer players who were professional, college, and high school athletes were included. The authors assessed the modified Harris Hip Score and Nonarthritic Hip Score preoperatively and at 6 months, 1 year, and 2 years after surgery. In addition, players were divided into groups according to radiographic evidence of OP and BME (2 groups each). Clinical outcomes, return to play, and radiographic assessments were compared between groups. Results: Twenty-eight hips met the inclusion criteria. The median modified Harris Hip Score significantly improved after hip arthroscopy (81.4, preoperatively; 95.7 at 6 months, P = .0065; 100 at 1 year, P = .0098; 100 at 2 years, P = .013). The median Nonarthritic Hip Score also significantly improved (75.0, preoperatively; 96.3 at 6 months, P = .015; 98.8 at 1 year, P = .0029; 100 at 2 years, P = .015). Furthermore, 92.0% of players returned to play soccer at the same or higher level of competition at a median 5.5 months (range, 4-15 months); 67.8% had radiological confirmation of OP; and 35.7% had pubic BME. The alpha angle was significantly higher in pubic BME group than the no–pubic BME group (64.8° vs 59.2°, P = .027), although there was no significant difference between the OP and no-OP groups. The prevalence of tenderness of the pubic symphysis significantly decreased preoperatively (32.1%) to postoperatively (3.6%). Magnetic resonance imaging findings confirmed that pubic BME disappeared in all players at a median 11 months (range, 6-36) after initial surgery. Conclusions: Arthroscopic management for FAI provides favorable clinical outcomes, a high rate of return to sports, and, when present, resolution of pubic BME among competitive soccer players.